Reasoning : Verbal and Non-Verbal:Useful for CAT, MAT, XAT, ATMA, JMET, GMAT, FMS, Hotel Management courses. SSC, Bank, Railway, IAS/PCS, B.Ed., etc. Also useful for Campus Interviews. - K.P. Singh (Source Books /Viva Books Private Limited, 2017)
The book Reasoning Verbal and Non-Verbal has been developed keeping in mind the increasing significance of reasoning as a major subject of study for various examinations, and dearth of useful materials on this subject in the market.